On learning about the missing Malaysian plane: a study on news diffusion - Syed Abdullah Idid, Syed Arabi (2015)

(untitled)
This is a study on how a tragic news about the Malaysian MH370 plane that lost ground contact in March 2014 was diffused among Malaysians. The unfortunate event of the missing flight is regarded as one of the unexpected significant events of the year. Malaysia Airlines flight 370, Boeing 777 flying from Kuala Lumpur to Beijing vanished on March 8, 2014 when it lost contact with the air traffic control at 2.40 am .Since then, the news of this event spread around the globe within a short period of time through the various types of media channels. Specifically, this study on the diffusion of news explores (1) the pattern in the spread of news from the time the news was announced,(2)compares the differences in terms of gender, race and age in learning about the news, 3)determines the medium most preferred by the audience in the spread of news and (4) identifies the pattern of interpersonal communication in the diffusion of news. A survey was conducted in the town of Kajang, among 500 adults through the use of a questionnaire. Data were analyzed using Statistical Package for Social Sciences (SPSS) WIN 20. Most of the respondents heard about the news around 7.00-8.00am when they were at home with television being the first source of news in knowing about the missing flight. Blogs and Twitter were two of the most common sources in spreading the news.